Migration flows: management practices of regulation in the local communities - Darya N. Stukalova, Anatoly V. Lubsky, Andrey V. Bedrik, Anton V. Serikov (Opción, 2019)
The authors analyze the experience of the Federal Republic of Germany in regulating migration flows in local communitieswith use ofcomparative-legal and sociological methodology. As a results, we can notice that the state provides an economic support for some groups to keep the balance of ethnic social structure and, therefore, implements some ideal representations of ethnic groups of the social consciousness using informational media. The authors concluded,the poor professional competence of the specialists of regional and municipal authorities and migration services makes it difficult to exercise the basic principles of value policy in the regulation of migration flows.